A Preliminary Assessment of Lichens in Different Landscapes of Hanoi, Vietnam - Hoang Ngoc Khac; Le Dac Truong; Nguyen Thi Hong Hanh; Nguyen Thi Hong Lien; Nguyen Quoc Binh; Vo Thi Phi Giao; Pham Hong Tinh; Bui Thi Thu (Diversity)
Hanoi is the capital of Vietnam, with a total area of 3359.82 km2 and a population of about 8.4 million people. This is one of the most developed cities in Vietnam, with an urbanization rate of 60%. In this study, we investigated how developed and urbanized areas may influence lichen diversity in Hanoi. The lichen community from Hanoi was studied using three tree stands from each of five landscapes: natural vegetation, industrial parks, urban and rural areas, and roadsides. Lichen species and their cover abundance were recorded on tree trunks at heights from 30 to 150 cm above ground in ten host trees that were randomly selected for each replication. Sixty-seven lichen species, from sixteen families and eight orders, were recorded. Results showed urbanization and the development of industrial parks and transportation altered species composition, evidenced by a reduced number of lichen species. Natural forests sustained the highest lichen diversity measured. These results suggest that a greater diversity of lichen can be preserved in natural forests, if that natural vegetation is effectively managed and conserved.